CHARACTERISTIC OF PROFESSIONAL PREPARATION CONTENT OF THE USA MOST COMMON MAJORS OF PARKS, RECREATION, LEISURE, AND FITNESS STUDIES DIVISION - S.V. Medynskyi (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: The given article deals with the phenomena of relative similarity of content components of the USA physical education field academic plans. Material: Undergraduate curriculum as the learning experiences of students in pursuit of a college degree is analyzed for the Parks, recreation, leisure, and fitness studies division. Data of the comparative analysis of curriculum content of the general education component, division field disciplines and the disciplines of major specialization are presented. Results: It is shown that the structure of curriculum at the USA universities has common and quite unified character and consists of three key components: general education, field disciplines and major courses. It was found that for the Parks, recreation, leisure, and fitness studies division these components are quite similar and display slight divergences not as much in the content of curricula as in the titles of the disciplines studied. Conclusions : It is recommended to examine in more detail the content of syllabi of the disciplines.